2013
DOI: 10.1007/s10549-013-2471-8
|View full text |Cite
|
Sign up to set email alerts
|

Incremental impact of breast cancer SNP panel on risk classification in a screening population of white and African American women

Abstract: Breast cancer risk prediction remains imperfect, particularly among non-white populations. This study examines the impact of including single nucleotide polymorphism (SNP) alleles in risk prediction for white and African American women undergoing screening mammogram. Using a prospective cohort study, standard risk information and buccal swabs were collected at the time of screening mammography. A 12 SNP panel was performed by deCODE Genetics. Five-year and lifetime risks incorporating SNPs were calculated by m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…In this University of Pennsylvania Institutional Review Board (IRB) approved, HIPAA compliant study, we retrospectively identified a cohort of women aged 40 years or older from our routine breast screening population who had also been prospectively recruited by a separate, IRB-approved, HIPAA compliant clinical study at our institution investigating the added value of genomic markers in breast cancer risk prediction [ 37 ]. For the purposes of our study, informed consent was waived, as this was a retrospective analysis and these women were already consented for research purposes in the original study [ 37 ] at the time of their recruitment. Each of these women was imaged as part of their routine screening with a full-field digital mammography (FFDM) system (Selenia Dimensions, Hologic Inc.) under a standard protocol.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this University of Pennsylvania Institutional Review Board (IRB) approved, HIPAA compliant study, we retrospectively identified a cohort of women aged 40 years or older from our routine breast screening population who had also been prospectively recruited by a separate, IRB-approved, HIPAA compliant clinical study at our institution investigating the added value of genomic markers in breast cancer risk prediction [ 37 ]. For the purposes of our study, informed consent was waived, as this was a retrospective analysis and these women were already consented for research purposes in the original study [ 37 ] at the time of their recruitment. Each of these women was imaged as part of their routine screening with a full-field digital mammography (FFDM) system (Selenia Dimensions, Hologic Inc.) under a standard protocol.…”
Section: Methodsmentioning
confidence: 99%
“…For each woman, information regarding the genotype of 12 SNPs were obtained from a commercially available assay based on Illumina Infinium II whole-genome genotyping (deCODE BreastCancer, deCODE genetics, Inc.) [ 37 ]. The deCODE SNP assay includes 12 genetic loci, specifically 2q35 ( rs13387042 ), MRPS30 ( rs4415084 ), FGFR2 ( rs1219648 ), TNRC9/TOX3 ( rs3803662 ), 8q24 ( rs13281615 ), LSP1 ( rs3817198 ), MAP3K1 ( rs889312 ), NEK10 ( rs4973768 ), 1p11 ( rs11249433 ), RAD51L1 ( rs999737 ), COX11/STXBP4 ( rs6504950 ), and CASP8 ( rs1045485 ), which have been consistently associated with either overall or subtype specific cancer risk, the risk for metastatic disease or age at diagnosis [ 39 - 49 ].…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, other genetic models include several single nucleotide polymorphisms (SNPs) in low penetrant genes, as they are more frequent in the general population and thus are preferable in the primary screening programs. Some models analyze 7 [73], 12 [74], 51 [72], 77 [75], 88 [76] or 153 SNPs [77]. However, the predictive ability of these genetic models, explained by an area under the ROC curve (AUC) is individually low, ranging from 0.53 to 0.68 [75,77].…”
Section: Genetic Profiling As a Tool For The Risk Assessmentmentioning
confidence: 99%
“…When combined multiplicatively with other risk models (i.e., BRCAT / Gail model), a substantial improvement in specificity and sensitivity was observed [72,73,76,78]. Addition of a genetic risk model (12 SNPs) to the BRCAT had a greater effect among African Americans than in whites as it reclassifies the high-risk status of several women undergoing screening mammography [74].…”
Section: Genetic Profiling As a Tool For The Risk Assessmentmentioning
confidence: 99%
“…McCarthy et al evaluated the performance of the BCRAT and the combined BCRAT+SNPs model using a cohort of African American and white women [55]. Agreement between the BCRAT and the BCRAT+SNPs model was low for identifying high-risk women.…”
Section: Review Of Existing Cancer Risk Prediction and Assessment Toomentioning
confidence: 99%